Population Changes of Eubacteria, Sulfate-Reducing Bacteria and Methanogenic Archaea in an Anaerobic Reactor Processing Ethanol Distillery Vinasse - Brown,Adis Ivonne Terry (2019)
Abstract The microbiological characterization by molecular techniques (DGGE and quantitative PCR) of Archaea, Bacteria domain and sulfate-reducing bacteria (SRB) from a laboratory scale Up-flow Anaerobic Sludge Blanket (UASB) processing sugar cane vinasse was performed during the operational phase with increasing organic loads. The organic load removal efficiency was between 97% and 75% for volumetric organic loads (VOL) in the range of 0.6 to 15.4 kgCOD.m-3.d−1 and for higher VOL (until 27.0 kgCOD.m-3 .d−1) the removal efficiency decreased to 48%. Archaea represented the majority of the estimated population (107 copies of 16S RNA ribosomal gene. mL-1) followed by bacteria (106 copies of 16S RNA ribosomal gene. mL-1) and sulfate-reducing bacteria (SRB) (105 copies of dsrB gene. mL-1). There was a significant difference between the populations of Archaea and SRB with increasing VOL. DGGE profiles show differences among populations with increasing VOL, especially with respect to sulfate-reducing bacteria. The presence of SRB together with a high sulfate removal percentage (97%) of about 15 kgCOD.m-3d-1h, indicates the establishment of a sulfidogenic process.